The Pandemic Push: Digital Technologies and Workforce Adjustments - Christina Gathmann; Christian Kagerl; Laura Pohlan; Duncan Roth (Institute of Labor Economics (IZA), 2023)
Based on a unique survey and administrative employer-employee data, we show that the COVID-19 pandemic acted as a push factor for the diffusion of digital technologies in Germany. About two in three firms invested in digital technologies, in particular in hardware and software to enable decentralized communication, management and coordination. The investments encouraged additional firm-sponsored training despite pandemic-related restrictions indicating that investments in digital technologies and training are complements. We then demonstrate that the additional investments helped firms to insure workers against the downturn during the pandemic. Firms that made additional investments relied less on short-time work, had more of their regular employees working normal hours and had to lay off fewer marginal workers. Male, younger and medium-skilled workers benefitted the most from the insurance effect of digital investments.
Keywords: D22; E22; J23; J63; 330; innovation; digital technologies; COVID-19; pandemic; investment; training; employment; worker flows